2016
DOI: 10.1002/ese3.140
|View full text |Cite
|
Sign up to set email alerts
|

Automatized analysis of IR‐images of photovoltaic modules and its use for quality control of solar cells

Abstract: It is well known that the performance of solar cells may significantly suffer from local electric defects. Accordingly, infrared thermography (i.p. lock-in thermography) has been intensely applied to identify such defects as hot spots. As an imaging method, this is a fast way of module characterization. However, imaging leads to a huge amount of data, which needs to be investigated. An automatized image analysis would be a very beneficial tool but has not been suggested so far for lock-in thermography images. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…To investigate defects in organic photovoltaics, thermal imaging as a fast, simple and cheap method for finding defects was applied [23,[35][36][37][38].…”
Section: Electrical Properties Of Imine and Simple Devices Together Wmentioning
confidence: 99%
“…To investigate defects in organic photovoltaics, thermal imaging as a fast, simple and cheap method for finding defects was applied [23,[35][36][37][38].…”
Section: Electrical Properties Of Imine and Simple Devices Together Wmentioning
confidence: 99%
“…Hauch et al demonstrated that an encapsulatingbarrier film having a water vapor transmission rate (WVTR) of 10 −3 g⋅m −2 ⋅day −1 @ 25 °C/40% RH may extend the life of organic solar cells to beyond 3 years [ 6 ]. As a common practice, encapsulating films are laminated from both sides of the solar cells and a lamination is used between flexible protective films [ 7 , 8 ]. It provides a device with a lifetime of several years under favorable circumstances, i.e., 25 °C/85% RH [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To analyse defects in, for example, solar cells, various techniques are used, however thermal imaging is a fast and simple method for locating defects [22,23,24,25]. In our work, a first time thermographic camera was used to detect the location of defects in the created devices and electrical behavior of imine and its hybrids with TiO 2 .…”
Section: Introductionmentioning
confidence: 99%